MicroRNA-877 contributes to decreased non-small cell lung cancer cell growth via the PI3K/AKT pathway by targeting tartrate resistant acid phosphatase 5 activity. Issue 23 (1st December 2020) - Bai, Xue; He, Changjun; Fu, Bicheng; Kong, Xianglong; Bu, Jianlong; Zhu, Kaibin; Zheng, Wei; Zhou, Fucheng; Ni, Boxiong
ABSTRACT: Non-small cell lung cancer (NSCLC) is a leading cause of cancer death in both men and women. microRNAs (miRs) can exert important functions in cancer development. However, the role of miR-877 in NSCLC as it relates to tartrate resistant acid phosphatase 5 (ACP5) is unknown. For this study, the gain-and-loss-of-function experiments were performed to explore the effects of miR-877 and ACP5 on NSCLC. miR-877 expression in LC and paracancerous tissues, lung epithelial cell line and NSCLC cell lines was detected, and the association between miR-877 expression and clinical features of LC patients was analyzed. The levels of ACP5, epithelial-mesenchymal transition (EMT) markers and apoptosis-related proteins were measured. In vivo experiments were conducted for further validation. Consequently, we found that miR-877 expression was lowered in LC tissues and cell lines, and correlated with clinical stage, differentiation, lymph node metastasis and prognosis of NSCLC patients. Additionally, miR-877 was determined to inhibit ACP5 activity, and miR-877 downregulated the PI3K/AKT pathway by silencing ACP5. Furthermore, overexpression of miR-877 inhibited the viability, migration, invasion and EMT of NSCLC cells, but promoted cell apoptosis. In conclusion, miR-877 overexpression inhibited malignant biological behaviors of NSCLC cells by downregulating ACP5 and inactivating the PI3K/AKT pathway.